Theme Based Features and Advantages of Various Health Monitoring Smartphone Applications (Apps) - Haniffa, Shahril Bin Mohamed; Chakravarthi, Srikumar; Karikalan, Barani (New Visions in Science and Technology Vol. 5, 2021)
Smartphone health apps show promising potential for monitoring chronic diseases and modifying health associated behaviours due to their incredibly high reach to the general public. These health apps could greatly reduce the burden of the health care system by enabling people to monitor their chronic conditions remotely from home, especially in recent times where there is a growing older population with chronic medical diseases like diabetes mellitus, cardiovascular disease, cancer and so on. In Spite of the concept of health apps being relatively new, it is recorded that patients with chronic medical conditions are increasingly using smartphone health apps to self-monitor their disease. In this article, we have discussed various features and benefits of smartphone health apps based on different themes such as medication monitoring, lifestyle management, alcohol regulation, diet control and others. We have also discussed if gaming features included in certain health apps increase effectiveness of smartphone health apps.